High Performance Control of Grid Connected Cascaded H-Bridge Active Rectifier Based on Type II-Fuzzy Logic Controller with Low Frequency Modulation Technique - M. Dabbaghjamanesh; A. Moeini; M. Ashkaboosi; P. Khazaei; K. Mirzapalangi (International Journal of Electrical and Computer Engineering (IJECE), 2016)
This paper tries to employ a fuzzy logic (FL) controller type II to control the Cascaded H-Bridge (CHB) active rectifier. This controller has strong performance, specially, when a low switching frequency Selective Harmonic Elimination (SHE) method is used. In order to regulate all of the DC link voltages, the optimum voltage balancing strategy in the low frequency modulation technique is used in the proposed method. Finally, the performance and effectiveness of the proposed method is validated in MATLAB environment.   All the simulation and result has been simulated by MATLAB software.